Pelatihan Pengelolaan SDM Di Era Digital Pada UMKM Di Perumahan Mega Regency Kabupaten Bekasi - Rismawati; Nasrullah; aziz setiawan; Dian Maharani; ira soliha (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
In the all-digital era, market competition is getting tougher, and many technology-based innovations and strategies have been developed by business people. From business planning techniques, product marketing techniques, to establishing a business image to the public are now wrapped in technology. However, not all of them are able to absorb and apply it in their business, including in the MSME sector. A lot of the culprits are outdated parents, or old-fashioned people who don't want to adapt. Therefore, to improve the quality and competitiveness of local businesses, Micro, Small and Medium Enterprises (MSMEs) need a digital-based training in an effort to improve competencies that are in line with the progress of the modern era. This training talks about how important it is to increase HR competencies for MSMEs in the digital era and how to utilize effective training in MSMEs in Mega Regency Housing, Bekasi Regency. The purpose of this training is to improve the application of digital technology in marketing management, operational efficiency, and innovation in employee development. The results of this training show a significant increase in the knowledge and skills of MSME actors, this training prepares them to compete in an all-digital market which is certainly very competitive. In this training, it is expected that close collaboration will be the key to success in improving MSMEs in Mega Regency Housing through improving the quality of human resources.